2017
DOI: 10.18775/ijmsba.1849-5664-5419.2014.32.1002
|View full text |Cite
|
Sign up to set email alerts
|

The Values of Virtual Brand Community Engagement of Facebook Brand Page

Abstract: Findings from both virtual brand community (VBC) behaviors provided a good reference, which informs a strategic direction to boost brand performance. The results examined different motives, which were likely to promote VBC participation, and were extended to the degree of VBC engagement. Both passive and active engagement results varied across community types, yet they both created significant brand loyalty and satisfaction providing theoretical and managerial implication into branding literature. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
1
3
0
1
Order By: Relevance
“…Considering the fact that engagement in virtual spaces creates a connection between consumers and the platform, the participatory behavior of the former can lead to loyalty (Casaló et al, 2010;De Vries & Carlson, 2014;Jing et al, 2017;Liu et al, 2019). Our hypothesis confirms the research of (Brodie et al, 2011;Von Doorn et al, 2010), which attests that loyalty is a strong consequence of engagement.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Considering the fact that engagement in virtual spaces creates a connection between consumers and the platform, the participatory behavior of the former can lead to loyalty (Casaló et al, 2010;De Vries & Carlson, 2014;Jing et al, 2017;Liu et al, 2019). Our hypothesis confirms the research of (Brodie et al, 2011;Von Doorn et al, 2010), which attests that loyalty is a strong consequence of engagement.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, data analysis indicated that consumer engagement plays the role of a complete mediating variable between motivational factors and loyalty. This is due to the need for continuous engagement and active participation to enhance consumer loyalty (Jing et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing engagement with a brand can be expected to contribute favorably to a brand’s performance in terms of sales growth, superior competitive advantage and profitability (Sashi, 2012). Furthermore, it has a positive impact on customer loyalty, satisfaction, empowerment, connection, emotional bonding, trust and commitment (Brodie et al , 2013; Jing et al , 2017). In fact, recent research by the Gallup Group indicates that engaged customers have a 23% premium in share of wallet, profitability, revenue and relationship growth in comparison to the average customer (Pansari and Kumar, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Merek Online. Jing et al, (2017) berpendapat bahwa para anggota komunitas menggunakan komunitas online tidak hanya untuk menyebarkan produk atau informasi perusahaan tetapi juga untuk menggunakan platform sebagai forum diskusi dengan mengunggah dan menjawab pertanyaan jika relavan. Menurut Casalo et al, (2007) komunitas online sebagai kelompok sosial yang hanya berkomunikasi dan berdiskusi melalui saluran internet.…”
Section: Komunitasunclassified